RANCANG BANGUN SISTEM INFORMASI PADA DILAUNDRYAJA! BERBASIS WEB - Saptony T (2023)
In the current laundry business services, there are various obstacles that are often experienced by consumers who experience problems in ordering laundry, namely customers who have ordered cannot know what the status of this laundry is in the process. So if you want to know the status of an order, you usually have to use a telephone or SMS. And if there are new customers who have never ordered, these customers must come to the place or call this laundry place to ask for information about the laundry service. Based on the survey I conducted so far, laundry does not have a modern information system and still uses a manual system. Overcoming the problems that exist in the laundry, an application will be made that can help the laundry business so that this application can provide the latest information to customers of laundry services that are informed to customers, provide shuttle services and information about promos in laundry that customers trust. To facilitate the process of making income reports quickly and accurately, provide the best service to laundry customers and reduce the occurrence of errors in the laundry. To improve services in this laundry business so that it can provide comfort and convenience in transactions. Then a Web-Based Laundry Service Ordering Information System was created which is expected to make it easier and provide convenience for laundry customers.